Health Literacy and Mortality: A Cohort Study of Patients Hospitalized for Acute Heart Failure. Issue 5 (May 2015) - McNaughton, Candace D.; Cawthon, Courtney; Kripalani, Sunil; Liu, Dandan; Storrow, Alan B.; Roumie, Christianne L.
Abstract : Background: More than 30% of patients hospitalized for heart failure are rehospitalized or die within 90 days of discharge. Lower health literacy is associated with mortality among outpatients with chronic heart failure; little is known about this relationship after hospitalization for acute heart failure. Methods and Results: Patients hospitalized for acute heart failure and discharged home between November 2010 and June 2013 were followed through December 31, 2013. Nurses administered the Brief Health Literacy Screen at admission; low health literacy was defined as Brief Health Literacy Screen ≤ 9. The primary outcome was all‐cause mortality. Secondary outcomes were time to first rehospitalization and, separately, time to first emergency department visit within 90 days of discharge. Cox proportional hazards models determined their relationships with health literacy, adjusting for age, gender, race, insurance, education, comorbidity, and hospital length of stay. For the 1379 patients, average age was 63.1 years, 566 (41.0%) were female, and 324 (23.5%) had low health literacy. Median follow‐up was 20.7 months (interquartile range 12.8 to 29.6 months), and 403 (29.2%) patients died. Adjusted hazard ratio for death among patients with low health literacy was 1.34 (95% CI 1.04, 1.73, P =0.02) compared to Brief Health Literacy Screen >9. Within 90 days of discharge, there were 415 (30.1%) rehospitalizations and 201 (14.6%) emergency department visits, with no evident association with health literacy. Conclusions: Lower health literacy was associated with increased risk of death after hospitalization for acute heart failure. There was no evident relationship between health literacy and 90‐day rehospitalization or emergency department visits.